Carbon nanotubes to outperform metal electrodes in perovskite solar cells via dopant engineering and hole-selectivity enhancement. Issue 22 (26th May 2020) - Jeon, Il; Shawky, Ahmed; Seo, Seungju; Qian, Yang; Anisimov, Anton; Kauppinen, Esko I.; Matsuo, Yutaka; Maruyama, Shigeo
Abstract : Triflic acid dispersed in an apolar solvent exhibited a superior doping effect and stability on carbon nanotube electrodes. The carbon nanotube electrode-based perovskite solar cells exceeded the metal electrode-based counterpart in terms of efficiency. Abstract : Triflic acid dispersed in an apolar solvent exhibited a superior doping effect and stability on carbon nanotube electrodes. By applying a high concentration of a hole-transporting material on the carbon nanotube top electrode in perovskite solar cells, higher power conversion efficiency than that of metal electrode-based perovskite solar cells was obtained.